Influence of angiotensin II receptor blocker combination tablet prescription on drug number and cost. (22nd December 2014) - Teramachi, Hitomi; Takahashi, Tatsuya; Tachi, Tomoya; Noguchi, Yoshihiro; Nagasawa, Hiroyuki; Ino, Yoko; Mizui, Takashi; Goto, Chitoshi; Tsuchiya, Teruo
Objectives: Combination therapy using an angiotensin II receptor blocker is expected to promote medication adherence and alleviate economic burden among patients by reducing the number of drugs taken, and thereby to lower associated medical costs. In the present retrospective study, we conducted a survey on the use of angiotensin II receptor blocker–containing combination tablets as anti-hypertensive drugs, in particular angiotensin II receptor blocker/diuretic and angiotensin II receptor blocker/calcium channel blocker combinations, in order to investigate the number of prescribed drugs and drug cost. Methods: We performed a retrospective study of patients who visited the outpatient clinic of GifuMunicipalHospital and received anti-hypertensive agents between June 2006 and December 2011. Results: No reductions in the number of prescribed drugs or drug cost were seen following a change in prescription to an angiotensin II receptor blocker/diuretic. Patients receiving an angiotensin II receptor blocker/calcium channel blocker had a significant reduction in the number of prescribed drugs and a slight decrease in drug cost. Conclusion: In this study, a reduction in the number of prescribed drugs and a decrease in economic burden were not observed after prescription of angiotensin II receptor blocker–containing combination tablets. In order to assess the usefulness of angiotensin II receptor blocker combination tablets, further studies are necessary to investigate their hypotensive effects, safety profile, and other factors.